Arbuscular mycorrhiza, rhizospheric microbe populations and soil enzyme activities in citrus orchards under two types of no-tillage soil management - Wang, P.; Zhang, J. J.; Xia, R. X.; Shu, B.; Wang, M.Y.; Wu, Q.S.; Dong, T. (Spanish Journal of Agricultural Research, 2011)
The arbuscular mycorrhizal (AM) status [total AM colonization (RLT), percentage of root length with arbuscules (RLA) and vesicles (RLV), spore density and hyphal length density], microbial populations and soil enzyme activities were investigated in citrus (Satsuma Mandarin grafted on Poncirus trifoliata L. Raf) orchards. Two types of no-tillage soil management, natural grass cover and use of herbicides, were employed in these orchards. The citrus AM colonization (37.26-70.09%) was high in all the experimental orchards sampled. The highest RLA (43.83%), spore density (384.63 spores/100 g soil), hyphal length density (4.09 m g–1 soil), rhizospheric microbial populations and enzyme activities were observed in the orchards with a natural grass cover, and the lowest values, except urease activity, were found in the orchards treated with herbicides. Spore density, hyphal length density, catalase activity and phosphatase activity varied notably between no-tillage/natural grass and no-tillage/herbicides treated orchards in the soil layers above 40 cm. A correlation analysis showed that the hyphal length density and organic matter were significantly positively correlated. Soil enzyme activities, except phosphatase, were strongly correlated with the bacteria populations. The data presented here demonstrates that the RLA, spore density, hyphal length density, rhizospheric microbe populations and enzyme activities were significantly better in the soil layers above 40 cm of orchards with a natural grass cover than herbicidetreated soils. So, the establishment of a natural grass cover benefits soil quality in citrus orchards in Southern China.